Complex structural rearrangements are present in high-grade dysplastic Barrett's oesophagus samples - Felicity Newell; Kalpana Patel; Michael Gartside; Lutz Krause; Sandra Brosda; Lauren G. Aoude; Kelly A. Loffler; Vanessa F. Bonazzi; Ann-Marie Patch; Stephen H. Kazakoff; Oliver Holmes; Qinying Xu; et al. (BMC, 2019)
Abstract Background Oesophageal adenocarcinoma (EAC) incidence is increasing and has a poor survival rate. Barrett's oesophagus (BE) is a precursor condition that is associated with EAC and often occurs in conjunction with chronic gastro-oesophageal reflux, however many individuals diagnosed with BE never progress to cancer. An understanding of the genomic features of BE and EAC may help with the early identification of at-risk individuals. Methods In this study, we assessed the genomic features of 16 BE samples using whole-genome sequencing. These included non-dysplastic samples collected at two time-points from two BE patients who had not progressed to EAC over several years. Seven other non-dysplastic samples and five dysplastic BE samples with high-grade dysplasia were also examined. We compared the genome profiles of these 16 BE samples with 22 EAC samples. Results We observed that samples from the two non-progressor individuals had low numbers of somatic single nucleotide variants, indels and structural variation events compared to dysplastic and the remaining non-dysplastic BE. EAC had the highest level of somatic genomic variations. Mutational signature 17, which is common in EAC, was also present in non-dysplastic and dysplastic BE, but was not present in the non-progressors. Many dysplastic samples had mutations in genes previously reported in EAC, whereas only mutations in CDKN2A or in the fragile site genes appeared common in non-dysplastic samples. Rearrangement signatures were used to identify a signature associated with localised complex events such as chromothripsis and breakage fusion-bridge that are characteristic of EACs. Two dysplastic BE samples had a high contribution of this signature and contained evidence of localised rearrangements. Two other dysplastic samples also had regions of localised structural rearrangements. There was no evidence for complex events in non-dysplastic samples. Conclusions The presence of complex localised rearrangements in dysplastic samples indicates a need for further investigations into the role such events play in the progression from BE to EAC.